2019
DOI: 10.1111/jcpt.13087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gastrointestinal adverse events with different doses of metformin in the treatment of elderly people with type 2 diabetes

Abstract: What is known and Objective: Gastrointestinal discomfort is the most common adverse event of metformin treatment for type 2 diabetes, especially in elderly patients.The aim of this study was to compare gastrointestinal adverse events resulting from different doses of metformin used for the treatment of elderly people with type 2 diabetes.Methods: A total of 361 elderly patients with newly diagnosed diabetes were randomly divided into three groups: metformin 1000 mg/d (N = 120), metformin 1500 mg/d (N = 121) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The frequency of pruritus vulvae with canagliflozin osmotic diuresis‐related AEs was increased compared with metformin, which is consistent with previous reports 46,47 . In the present study, the incidence of AEs with metformin treatment was much higher than that in other trials, but is consistent with a previous study on elderly Chinese people with diabetes, which showed that 196 patients (54.3% of the study population) experienced at least one AE 48 . This phenomenon of high AE incidence in the present study may be explained by the all‐female study population and the presence of comprehensive records (including temporary response) and information bias, since this study was open‐label.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The frequency of pruritus vulvae with canagliflozin osmotic diuresis‐related AEs was increased compared with metformin, which is consistent with previous reports 46,47 . In the present study, the incidence of AEs with metformin treatment was much higher than that in other trials, but is consistent with a previous study on elderly Chinese people with diabetes, which showed that 196 patients (54.3% of the study population) experienced at least one AE 48 . This phenomenon of high AE incidence in the present study may be explained by the all‐female study population and the presence of comprehensive records (including temporary response) and information bias, since this study was open‐label.…”
Section: Discussionsupporting
confidence: 92%
“…46,47 In the present study, the incidence of AEs with metformin treatment was much higher than that in other trials, but is consistent with a previous study on elderly Chinese people with diabetes, which showed that 196 patients (54.3% of the study population) experienced at least one AE. 48 blood pressure, whereas a previous study showed that no blood pressure changes were demonstrated in PCOS patients taking empagliflozin. 24 Third, given that this study was designed as a single-centre, open-label study, and not a multicentre, blinded study, our findings, particularly those pertaining to the multiple secondary outcomes investigated, might be attributable to chance.…”
Section: Discussionmentioning
confidence: 62%
“…15,56 The most common side effects of metformin are abdominal pain, bloating, nausea, and diarrhea, which can be mitigated by dose titration or extended-release preparations. 57 Our searches returned no studies directly examining the effect of metformin on parameters of reflux. Famotidine may improve the bioavailability and simultaneously enhance the renal clearance of metformin, and may transiently augment metformin's hypoglycemic effects.…”
Section: Non-fda Approved Medicationsmentioning
confidence: 99%
“…Patients enrollment and study protocol 50 antidiabetic agents treatment-naïve patients with newly diagnosed type 2 diabetes, aged≥60 years, with body mass index≥18.5 kg/m 2 and Hemoglobin A1c (HbA1c) of 7.0%-9.0% were enrolled from a previous study (7). The exclusion criteria included the following: (a) confirmed or suspected type 1 diabetes; (b) previous treatment with insulin or other antidiabetic drugs for more than 14 days; (c) a history of known peptic ulcers, Helicobacter pylori infection, gastrointestinal surgery, chronic gastritis, gastrointestinal tumor or severe gastrointestinal discomfort; (d) current (within 3 months of screening) diabetic ketoacidosis or hyperosmolar coma; (e) current cardiovascular disease or other serious disease; (f) a creatinine clearance rate <60 mL/min; (g) liver enzymes more than 2 times the upper limit of normal at screening; (h) use of unknown combination drugs; and (i) poor drug compliance.…”
Section: Methodsmentioning
confidence: 99%